PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN, PERTUMBUHAN DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2010 â 2012 - Muhammad Nur Fuin, 10.05.51.0134 (Students Journal of Economic and Management, 2013)
Debt policy is an important policy for the company in managing the debt. A growing ompany requires a larger capital. The capital can be obtained from debt or private equity. Debt policy can be influenced by various factorsthat occur in an company, namely, institutional ownership, company size, company growth and rofitability. The purpose of this study was to analyze the effect of institutional ownership, size of company, company growth andprofitability to debt policy. Population andÂ  ample in this research is manufacturing company listed on BEI 2010 â 2012. Sample retrieval technique is purposive sampling and obtained samples some 252 companies. Typethe data is secondary. Data collecting Method use documentation. Analysis technique used is multiple regression. The result analysis by the se of multiple regression show that: ( 1 ). Institutional ownership not affect to debt policy. ( 2 ). Company size affect positive to debt policy. ( 3 ). Company growth affect positive toÂ  ebt policy. ( 4 ). Profitability affect positive to debt policy. Keyword : Institutional Ownership, Company Size, Company Growth, Probability, Debt Policy